PERSPECTIVES OF PRODUCTION AND USING OF METALLIZED RAW MATERIALS FOR PRODUCTION OF HIGH-QUALITY GRADES OF STEEL. Message 2. Peculiarities of using of metallized raw materials in conditions of steel melting in electric slug furnaces - V. I. Timoshpolskij; I. N. Plushchevskij; I. A. Trusova; S. V. Korneev (Литьë и металлургия, 2009)
The peculiarities of using of metallized raw material in conditions of steel melting in arc furnaces are shown.